Isu Mutakhir : Faktor-Faktor Kesiapsiagaan Perawat Dalam Pencegahan Kebakaran di Rumah Sakit - Nazua Nabila; Susilawati Susilawati (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
A hospital is a complex, multifaceted, integrated medical facility in the modern healthcare system. Hospitals that provide comprehensive medical services that include the prevention, diagnosis, treatment, and rehabilitation of various health conditions are called hospitals. The risk of fires is high in hospital buildings because of the use of electrical equipment that causes short circuits and tubes containing gases and chemicals that can cause fires. The presence of patients with fragile health conditions, complex medical equipment, and various chemicals makes hospitals vulnerable to fire. Fire protection refers to the actions taken to respond to fire hazards in hospitals. Preparedness is a collection of actions aimed at preventing disasters by organizing and implementing appropriate and effective actions. The purpose of this study is to identify factors related to the readiness of nurses to deal with fire risks. This study uses the systematic literature review (SLR) method to assess the factors and what precautions are taken to overcome fires in hospitals. The SLR method was chosen because it is used to summarize, explore, disseminate, and comprehensively interpret recent research findings on the topic.